DAMPAK GAJI TERHADAP MOTIVASI KERJA GURU AGAMA KRISTEN DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Macareno Sendi Yudiarto; Desire Karo Karo (STAK Anak Bangsa, 2021)
Abstracts: Educational success cannot be achieved without cooperation between the various components involved. Educational implementers such as school principals, teachers and students are factors that greatly determine the level of quality of an education. The problems that arise are: What is meant by teacher salary? How do Christian religious teachers work motivation? The Impact of Salary on the Work Motivation of Christian Teachers? What are the factors that influence the salary of Christian teachers' work motivation? The answers are: (1) Salaries are not wages, but professional positions. Someone who receives a salary usually has strong work ties with the organization. When the salary is received, it is done regaularly at the beginning of each month. (2) Motivation as a condition that moves people towards a specific goal and a skill in directing employees to work optimally so that their desires can be achieved properly. (3) The impact of salary on Christian religious teacher work motivation is very significant. The smaller the salary, the smaller the results because in carrying out their teaching and learning duties, the teacher really needs infrastructure. (4) Factors that affect teacher work motivation are: pressure, motive, desire and desire to carry out activities, encouragement and need to carry out activities, hopes and ideals, self-respect and respect, and interesting activities. Abstrak: Keberhasilan pendidikan tidak dapat digapai tanpa adanya kerjasama antar berbagai komponen yang terkait. Para pelaksana pendidikan seperti kepala sekolah, guru dan murid merupakan faktor yang sangat menentukan tinggi rendahnya kualitas dari suatu pendidikan. Persoalan tyang timbul adalah: Apakah yang dimaksud dengan gaji guru? Bagaimana motivasi kerja guru Agama Kristen? Dampak Gaji terhadap Motivasi Kerja Guru Agama Kristen? Faktor-faktor apa sajakan yang Mempengaruhi Gaji terhadap Motivasi Kerja Guru agama Kristen? Jawanya adalah: (1) Gaji (salaries) bukan upah (wages), melainkan jabatan profesi. Seseorang yang menerima gaji biasanya memiliki ikatan kerja yang kuat dengan organisasinya. Waktu penerimaan gaji dilakukan secara rutin tiap awal bulan. (2) Motivasi sebagai suatu kondisi yang menggerakan manusia k earah suatu tujuan tertentu dan suatu keahlian dalam mengarahkan pegawai agar mau bekerja secara maksimal sehingga keinginan-keinginan bisa tercapai dengan baik. (3) Dampak gaji terhadap motivasi kerja guru Agama Kristen sangat signifikan. Gaji yang semakin kecil maka hasil semakin kecil karena dalam melaksanakan tugasnya belajar mengajar guru sangat memerlukan sarana prasana. (4) Faktor yang mempengaruhi motivasi kerja guru adalah: desakan, motif, adanya hasrat dan keinginan untuk melakukan kegiatan, adanya dorongan dan kebutuhan melakukan kegiatan, adanya harapan dan cita-cita, penghargaan dan penghormatan atas diri, serta adanya kegiatan yang menarik.